2020
DOI: 10.1371/journal.pone.0226761
|View full text |Cite
|
Sign up to set email alerts
|

An accurate, precise, and affordable light emitting diode spectrophotometer for drinking water and other testing with limited resources

Abstract: Spectrophotometers are commonly used to measure the concentrations of a wide variety of analytes in drinking water and other matrixes; however, many laboratories with limited resources cannot afford to buy these very useful instruments. To meet this need, an accurate, precise, and affordable light emitting diode (LED) spectrophotometer was designed and built using best engineering practices and modern circuit design. The cost and performance of this LED spectrophotometer was compared against 4 common commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Submersible spectrophotometer sensors, widely used for drinking water quality monitoring (e.g. D' Acunha and Johnson 2019;González-Morales et al 2020;Prairie et al 2020), may, however, offer a reliable means to provide data on SS fingerprint properties at high frequency. Bass et al (2011) and Martínez-Carreras et al (2016) used submersible spectrophotometer sensors, measuring absorbance in the ultraviolet visible (UV-VIS) range, to estimate SS properties in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Submersible spectrophotometer sensors, widely used for drinking water quality monitoring (e.g. D' Acunha and Johnson 2019;González-Morales et al 2020;Prairie et al 2020), may, however, offer a reliable means to provide data on SS fingerprint properties at high frequency. Bass et al (2011) and Martínez-Carreras et al (2016) used submersible spectrophotometer sensors, measuring absorbance in the ultraviolet visible (UV-VIS) range, to estimate SS properties in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Latorre et al (2019) recommended comparing the results using the PAN method against a more accurate method such as ICP‐MS to validate results. An LED‐spectrophotometer designed and built by Prairie et al (2020) used the PAN method at 560 nm, and found comparable results to the Hach DR‐2700, Hach 2010 and Thermal Electron Spectronic 20D+. Even though the PAN method promises low range Mn detection (0–0.700 mg/L, Method 8149), high levels of metals would still interfere with Mn (Hach, 2014).…”
Section: Emerging Methods For Field‐testingmentioning
confidence: 96%
“…The light-emitting diode (LED) is a very good example because LED is environmentally friendly, easy to control its parameters, besides, LED has long-life use and provides a good quality of light [ 1 , 30 ]. More importantly, LED has a narrow full width at half maximum (FWHM) and produces less heat [ 31 ]. Thus, LED is an ideal illumination source for accurate investigation on the effects of light on Neurospora crassa .…”
Section: Introductionmentioning
confidence: 99%